MANAJEMEN PENGEMBANGAN KURIKULUM MUATAN LOKAL DI RA NU BANAT KUDUS - Siti Fadlilah (Intelegensia : Jurnal Pendidikan Islam, 2018)
AbstractThis research aimed to describe the planning, organization, implementation, and evaluation of local content curriculum development at RA NU Banat Kudus. This research used qualitative approach and belongs to descriptive design. Data collection was done through observation, in depth interview, and documentation. The data was then analyzed by using triangulation technique. The research results showed that: 1) planning of local content curriculum development at RA NU Banat Kudus is done in the beginning of academic year and the material of local content is adjusted to the curriculum of Religion Ministry of Kudus. 2) Organizing of local content curriculum development classified by students’ age and taught classically in the classroom. 3) The implementation of development including the characteristic of local content curriculum (scope of teaching material, purpose, function, etc.) and implementation strategy. 4) Evaluation of local content curriculum development in learning process is done every day (daily achievement scale).Keywords: Curriculum Management, Curriculum Development, Local Content